Hungarian Monitoring, 10 February 1989 . [Magyar rádiófigyelő], 1989. február 10 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On the integration of demobilized Soviet soldiers - Roundtable talks and wave of strikes continue in Poland - Hard-line statement in Prague on the opposition, terrorists - Soviet election campaign - New chair of the American Democratic Party - Developments in Afghanistan - Iraq-Iran relations Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee session discusses question of domestic politics - Hungarian Democratic Forum (MDF) writes letter to Gorbachev - Dr József Bielek elected as president of Budapest council - World Exposition - Can Hungarian Socialist Workers' Party (MSZMP) be driven from power? - Conversation on intellectuals' existence in socialism Economy: - World Bank loans Hungary USD 140 million to transform industry - Hungarian-West German, Hungarian-Austrian relations Külpolitika: - A leszerelt szovjet katonák beilleszkedéséről - Folytatódik a kerekasztal és a sztrájkhullám Lengyelországban - Kemény kijelentés Prágában az ellenzékről, a terroristákról - A szovjet választási kampány - Az amerikai Demokrata Párt új elnökéről - Az afganisztáni fejleményekről - Az iraki-iráni kapcsolatok Belpolitika: - MSZMP KB ülés aktuális belpolitikai kérdésekről - Gorbacsovnak írt levelet az MDF - Dr. Bielek Józsefet választották meg a fővárosi tanács elnökévé - A világkiállítás ügye - Kiszorulhat-e a hatalomból az MSZMP? - Beszélgetés az értelmiségi létről a szocializmusban Gazdaság: - A Világbank 14o millió dolláros kölcsönt folyósít Magyarországnak az ipari szerkezet átalakítására - Magyar-NSZK, magyar-osztrák kapcsolatok